2017
DOI: 10.4269/ajtmh.16-0309
|View full text |Cite
|
Sign up to set email alerts
|

Human Granulocytic Anaplasmosis as a Cause of Febrile Illness in Korea Since at Least 2006

Abstract: Human granulocytic anaplasmosis (HGA) is a tick-borne rickettsial zoonosis with fever, thrombocytopenia, and leukopenia. HGA has been reported in Korea in 2013 but it is uncertain how long it has existed. A retrospective study was conducted on patients who underwent bone marrow examination due to fever and cytopenia, with no clear hematologic or microbiologic causes, from 2003 through 2012. Laboratory diagnosis was made by detecting 16S rRNA genes of Anaplasma phagocytophilum from the stored blood samples. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…We did not observe any scrub typhus and SFTS co-infections, in contrast to a previous study 7. As our study samples were collected in 2006, and it is uncertain whether there was a sufficient concurrent epidemic of SFTS in Korea, in contrast to the presence of HGA at least since 2006 6. Another possible explanation is that there is a possibility of false negatives in few cases because laboratory detection of another gene of SFTSV, such as S segment or M segment, was not performed.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…We did not observe any scrub typhus and SFTS co-infections, in contrast to a previous study 7. As our study samples were collected in 2006, and it is uncertain whether there was a sufficient concurrent epidemic of SFTS in Korea, in contrast to the presence of HGA at least since 2006 6. Another possible explanation is that there is a possibility of false negatives in few cases because laboratory detection of another gene of SFTSV, such as S segment or M segment, was not performed.…”
Section: Discussioncontrasting
confidence: 84%
“…Severe fever with thrombocytopenia syndrome (SFTS) and human granulocytic anaplasmosis (HGA) are emerging tick-borne infections in Korea 123. The emergence of both infections in Korea can be traced back to 2008 and 2006, respectively 456…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is unclear whether or not our patient had HLH. Nonetheless, since being first described in a case series of 29 patients in 2007 by Dumler et al, 25 HGA-induced HLH has been reported in New York, 42 South Korea, 43 and Greece. 44 It is essential to identify HGA and other tick-borne diseases as an inciting cause of HLH.…”
Section: Discussionmentioning
confidence: 98%
“…Many previous studies based in Korea have focused on anaplasmosis in animals other than humans,45 indicating a long-term interest in the disease. Since the first HGA case was reported in 2013,2 few cases have been reported in Korea 6…”
mentioning
confidence: 99%
“…There are similar animal hosts between HGA and HFRS. A. phagocytophilum have been detected in ticks including H. longicornis , Ixodes nipponensis , and I. persulcatus and in wild animals such as striped field mice and the major host of Hantan virus is wild rodents ( Apodemus species) 6…”
mentioning
confidence: 99%